The Paradigmatic Bases of the Global Competitive Leadership - Shlapak Alla V. (Bìznes Inform, 2019)
The article is aimed at defining the paradigmatic principles of the global competitive leadership. The dynamics of volumes of the world exports, clearly expressed in the growth rate of the world trade and growth rate of global gross domestic product, are displayed. The growth of capitalization of the world financial market is indicated, where diversification of the instrumental structure and increase of volumes of financial transactions are carried out by the economic agents of different national affiliation. The fundamental influence of technoglobalism on the expansion of sources of the competitive leadership of countries is indicated, which is manifested primarily in the intensification of the interstate scientific-technological exchange and the rapid interregional diffusion of the scientific-technological developments and innovations. Pointed out is the multidimensional influence of institutionalization on the mechanism of the competitive leadership of countries through active development of a branched system of supranational institutions of regulation of all subsystems together with the structural components of the world economy. A powerful consolidating influence on the processes of development of the global market system of the global market as such, global demand and supply is characterized. The vector orientation of providing competitive leadership of the countries with its reorientation from the national trajectory to the regional and global ones is analyzed. It is concluded that the global phase of the world economic development radically transforms all the constituent elements of the philosophy of development of competitive leadership.